Oxidative stress and lipid peroxidation-derived DNA-lesions in inflammation driven carcinogenesis - Bartsch, Helmut; Nair, Jagadeesan (Cancer detection and prevention, 2004)
During chronic inflammatory processes an excess of free radicals and DNA-reactive aldehydes from lipid peroxidation (LPO) are produced, which deregulate cellular homeostasis and can drive normal cells to malignancy. Etheno (ɛ)-modified DNA bases are generated by reactions of DNA with a major LPO product, trans-4-hydroxy-2-nonenal. We investigated steady state levels of ɛ-DNA adducts in organs, blood or urine from patients with cancer prone diseases, especially when related to persistent inflammatory processes. We have developed sensitive and specific methods for adduct detection in vivo. Hepatic etheno-adduct levels were significantly elevated in patients with Wilson's disease and primary hemochromatosis. Excess storage of copper/iron causing oxidative stress and LPO-derived DNA-damage, are implicated in disease pathogenesis as confirmed by studies in LEC-rats, a model for Wilson's disease. When patients with alcohol related hepatitis, fatty liver, fibrosis and cirrhosis were compared with asymptomatic livers, excess hepatic DNA-damage was seen in all patients, except those with hepatitis. Etheno-deoxyadenosine excreted in urine was measured in HBV-infected patients diagnosed with chronic hepatitis, cirrhosis and hepatocellular carcinoma: as compared to controls, patients had 20-90-fold increased urinary levels. In conclusion: ɛ-DNA adducts may serve as potential markers for assessing progression of inflammatory cancer-prone diseases. Also the efficacy of human chemopreventive interventions could be verified by using our non-invasive urine assay. Mechanisms and host-factors that influence the steady-state levels of ɛ-DNA adducts in cancer prone tissues are under investigation.